Extratropical cyclone climatology across eastern Canada. (24th September 2014) - Plante, Mathieu; Son, Seok‐Woo; Atallah, Eyad; Gyakum, John; Grise, Kevin
ABSTRACT Extratropical cyclone (ETC) tracks across eastern Canada are examined by applying a Lagrangian tracking algorithm to the lower‐tropospheric relative vorticity field of reanalysis data. Both the seasonal cycle and the interannual variability of ETCs are quantified in terms of overall cyclone frequency, intensity, and regions of development and decay. We find that ETCs travelling to eastern Canada tend to develop over the Rockies, the Great Lakes and the US East Coast. The ETCs are most intense over Newfoundland and the North Atlantic Ocean, confirming previous findings. While ETCs at cities along the Atlantic coastline (e.g. St. John's) are dominated by East Coast cyclones (which are intense in winter), those inland (e.g. Toronto) track primarily from the Great Lakes. ETCs that develop over the Gulf of Mexico affect eastern Canada infrequently, but those that do tend to be intense. The interannual variability of the wintertime ETCs is influenced by the El Niño‐Southern Oscillation (ENSO). Significant ENSO‐related variability is found over most regions of southern Canada, except on the east coast. Although ETCs at Toronto are significantly modulated by ENSO, no visible changes are found at St. John's. These ENSO‐related ETC changes are mostly due to the shifts in ETC development regions, with minor changes in the travelling direction of ETCs.